Bypassing Birth Centres for Childbirth: an Analysis of Data from a Community-Based Prospective Cohort Study in Nepal - Karkee, R.; Lee, Andy; Binns, Colin (Oxford University Press, 2015)
Background: In Nepal, women residing in rural areas tend to bypass local birth centres and deliver at urban hospitals, despite the availability of obstetric care in these centres. This study investigated the incidence of bypassing, characteristics of bypassers and their reasons for bypassing the birth centres. Methods: A prospective cohort study was undertaken in the Kaski district of central Nepal. The 353 pregnant women of 5 months or more gestation recruited from the community had access to local birth centres. They were interviewed at baseline using a structured questionnaire, and were followed up within 45 days post-partum. Comparisons were made between women who delivered at birth centres and those who gave birth at hospital. Logistic regression analysis was performed to determine the factors affecting the risk of bypassing. Results: Of the final sample of 258 participants who delivered in a health facility, 181 women (70.2%) bypassed their nearest birth centres to deliver at hospitals. Bypassers tended to be wealthy and have intrapartum complications, but the likelihood of bypassing apparently decreased by higher parity and frequent (four or more) antenatal care visits. Availability of operating facility, adequacy of medical supplies and equipment and competent health staff at the facility were the main reasons for their bypassing decision. Conclusions: The risk of bypassing for childbirth was high in central Nepal. Provision of quality and reliable emergency obstetric services together with well trained and competent staff at birth centres are recommended to reduce bypassing and pressure on the public hospital system.